Traumatic dislocation of the S1 polyaxial pedicle screw head: a case report - Du Plessis, Pieter N. B. (J Spine Surg, 2017)
Polyaxial screw head dislocation in the absence of a manufacture defect is extremely rare and represents a biomechanical overload of the screw, leading to early failure. A 58-year-old gentleman underwent instrumented fusion using polyaxial pedicle screws-titanium rod construct with interbody cage for spondylolytic spondylolisthesis at the L5/S1 level. He attempted to bend forward ten days after the surgery which resulted in a dislocation of the right S1 polyaxial screw head from the screw shank with recurrence of symptoms. He underwent revision surgery uneventfully. This case highlights the need to pay particular attention to the strength of fixation and the amount of release to avoid such a complication.